Meningkatkan Nasionalisme dan Spiritualitas Anak Jalanan dengan Program Pembelajaran Anak Negeri - Abdillah dkk, Diaz Syafrie (Al-Insyiroh: Jurnal Studi Keislaman, 2018)
Street children are children who spend most of their time earning a living, wandering the streets or other public places. This program is an innovation in the field of community service called the "Children of the Country" learning program. This program is directed to meet the Indonesian golden generation of 2045 by increasing nationalism and spirituality for street children in the country of children. This program consists of two major parts, namely brief material delivery and educational games. To prove the success of the community service program, pre-test and post-test were conducted. Personality charts show the nationalism and spirituality of program participants increased. Thus, it can be said that this community service program was declared successful in welcoming the Indonesian golden generation of 2045